1991
DOI: 10.1088/0029-5515/31/1/001
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous ion heating in REPUTE-1 ultra-low q and reversed field pinch plasmas

Abstract: Measurements of ion and electron temperatures on REPUTE-1 ultra-low q (ULQ) and reversed field pinch (RFP) plasmas have revealed that the ion temperature is higher than the electron temperature and that the impurity ion temperature exceeds the hydrogen ion temperature. In ULQ plasmas the impurity ion temperature is correlated with the amplitude of the magnetic field fluctuations observed outside the plasma. A model on ion heating by fluctuations is found to explain the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…The same phenomenon is observed in experimental plasmas 5,28 in which a MHD relaxation controlled by collisionless or collisional magnetic reconnection takes place. This phenomenon is considered to be associated with the generation of collisionless ion viscosity, which leads directly to the ion heating.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The same phenomenon is observed in experimental plasmas 5,28 in which a MHD relaxation controlled by collisionless or collisional magnetic reconnection takes place. This phenomenon is considered to be associated with the generation of collisionless ion viscosity, which leads directly to the ion heating.…”
Section: Introductionsupporting
confidence: 77%
“…Since the existence of the longitudinal magnetic field makes a plasma less compressible, this result indicates that the plasma compressibility is a key factor in determining the behavior of driven reconnection. The anomalous ion heating is often observed in experimental plasmas 5,28 in which a MHD relaxation controlled by magnetic reconnection takes place. This paper may give an explanation of this phenomenon.…”
mentioning
confidence: 99%
“…Further, inequality ͑55͒ shows that this mechanism of the ion heating probably makes the ion temperature higher than the electron's. That the temperature of the heavier ions is higher than that of the lighter ones, as observed in the experiment, 13 is a more straightforward corollary of the set of Eqs. ͑16͒ and ͑17͒: ͗͑ϩ͒"U:"U͘ represents the ion heating power per unit mass of plasma; hence the heavier ions are more strongly heated.…”
Section: ␤ϳ ͑52͒mentioning
confidence: 52%
“…It is also observed that there exists anomalous plasma resistance and the temperature of heavier ions is higher than that of the lighter ones. [8][9][10][11][12][13][14][15] Since the only external heating is ohmic, the classical ion energy input is from collisional equipartition with the electrons. This process always causes T i ϽT e , owing to the second law of thermodynamics.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation